Trilhos da educação e do português em Angola - Neves, Catarina (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The education system in Angola has undergone reforms since 1975. However, the aimed goal has not been reached in the fragile context of the end of 20th century and the beginning of the 21st century, and we still can find some inherited constraints from the past . Weaknesses in the Portuguese language, associated with the non-use of national languages in teaching and learning, are still aspects to overcome. Differently from the majority of African countries, the former colonial language has gained in Angola an unique strength. Being adopted as the of?cial language after Angola’s independence, Portuguese has assumed to be the schooling language from Cabinda to Cunene. However, its teaching-learning faces several obstacles, along with the national languages, in a framework of post-con?ict and social, cultural and economic reconstruction. The debate around the status of Portuguese in Angola and the introduction of national languages in the educational curriculum should contribute to the development of the education system, due to its effects on curricula design, teacher training and literacy programs.